A representação da Comuna de Paris nas obras de Gustave Flaubert e Emile Zola - Pereira, Maria Iracema Giannella Abreu (2025)
The aim of this study is to analyze, the reaction and the representation of the two best French writers of the XIX century, Gustave Flaubert (1821-1880)and Émile Zola (1840-1902), done regarding one of the most outstanding and important political events of Modernism: The Paris Commune(1871). The study starts with Flaubert´s epistolary work, through the analysis of twenty-three letters written by Flaubert in 1871, as well as his novel The Sentimental Education; and next to Zola, of the La Cureé and L´Assommoir novels. We will therefore proceed examining this material, trying to clarify as adequately as possible how these two main authors of the nineteenth century French prose understood the Commune, and incorporated it into their writings. As a historical contextualization, with a theoretical foundation according to Bibliographical References here mentioned, I deal with the so called 1848 Revolution, Napoleon III´s accession, the urban reform of Paris, the Franco-Prussian war, and Napoleon´s fall. I approach the Commune as a result of various specific factors of the period: a national crisis of the Bonaparte regime, the turmoil caused by the Franco-Prussian war, and, mainly the rise of the ideology and of the political development of socialist ideals among the European proletariat, expressed through the expansion of the International Workers´ Association (IWA)